'Trust me, I'm a doctor': a qualitative study of the role of paternalism and older people in decision-making when they have lost their capacity. (December 2017) - Cole, Joanne; Kiriaev, Oleg; Malpas, Phillipa; Cheung, Gary
Objective: The objective of this study was to explore whether older people want their doctors to make treatment decisions on their behalf when they no longer have capacity to do so, and their reasons for these preferences. Method: A convenience sample of older people from two retirement villages were interviewed and asked to respond to a hypothetical vignette. Their responses were analysed using qualitative thematic methodology. Results: Thirty-seven people (56.8% female; mean age = 83.9 years; mean Mini Mental State Examination = 26.5) participated; 73.0% indicated that they would want their doctor to make treatment decisions on their behalf. Three key themes emerged: 1) trust in the doctor–patient relationship; 2) doctor-derived factors: knowledge and expertise, professionalism, role and responsibility; 3) patient-derived factors: vulnerability, dependence and reliance, compromised autonomy. Conclusion: Our findings suggest that the paternalistic model within medical care can be an expectation of some older patients and if taking a paternalistic approach we should not underestimate the trust and power that is imparted to us.